Characteristics of Takokak (Solanum torvum Sw.) Leaves Herbal Tea Based on Drying Temperature - I Gede Arie Mahendra Putra; Putu Julyantika Nica Dewi; Dewa Ayu Anom Yuarini; Muhammad Eriansyah Al Hakim; Ida Bagus Gede Mahatmananda (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Pokak plant, also known as takokak or prickly nightshade (Solanum torvum Sw.), belongs to the Solanaceae family. The part of the plant commonly utilized was its leaves. Takokak leaves contained numerous bioactive components that can be developed into one of the functional foods, such as herbal tea. One crucial aspect in the herbal tea-making process is the drying temperature. The aimed of this research was to investigate the effect of drying temperature variations on the characteristics of takokak leaves herbal tea and to determined the optimal temperature that can yield the best characteristics of takokak leaf herbal tea. Parameters observed in this study included total phenols, total flavonoids, total tannins, vitamin C, antioxidant activity, and sensory properties comprising hedonic tests on color, taste, aroma, and overall acceptances. Data obtained were analyzed using analysis of variance (ANOVA), and if there was a significant effect of treatment on the results (P<0.05), it would be followed by the Tukey test. The results showed that variations in drying temperature significantly affected the values of total phenols, tannins, flavonoids, vitamin C, antioxidant activity, and sensory properties regarding color, aroma, taste, and overall acceptances of takokak leaf herbal tea. The best treatment was obtained at a drying temperature of 40°C with total phenol content of 31.58 mg GAE/g, total tannin content of 0.79 mg TAE/g, total flavonoid content of 14.23 mg QE/g, total vitamin C content of 7.92 mg AAE/g, antioxidant activity of 84.26%, and sensory properties for color, aroma, taste, and overall acceptances respectively were 5.73 (like), 5.27 (slightly like), 3.77 (neutral), and 3.91 (neutral).